Relación entre contrato psicológico y desempeño laboral de empleados en empresas públicas y privadas - Cruz Rojas, Mirtha Alejandra (2021)
Human resources practices are involved when facing social and economic changes, among others, affecting their labor relations and the stability of their personnel, impacting the job performance of workers. When an individual subscribes to a formal contract, he also initiates the psychological contract. This has a social-emotional character, referring to the fulfillment of reciprocal and implicit obligations between employee-employer. The objective was to identify the relationship between the psychological contract and the job performance in employees of public and private companies through an applied review. The search for articles was carried out following the PRISMA guidelines (Urrútia & Bonfill, 2010), making use of the Science Direct thesaurus for the selection of keywords. In addition, considering the eligibility criteria, the Scopus and Proquest databases were used. Seven articles were selected, which evaluated the relationship between the psychological contract and job performance in the business context. In general, the measures of fulfillment of the psychological contract were related to an increase in job performance. Future research should improve the standardization of instruments with higher methodological quality and focus efforts on adapting human resources programs to dynamic contexts.